Improved Complex Skill Acquisition by Immersive Virtual Reality Training: A Randomized Controlled Trial - Lohre, Ryan; Bois, Aaron J; Athwal, George S; Goel, Danny P (Journal of bone and joint surgery. American volume, 2020)
There has been limited literature on immersive virtual reality (VR) simulation in orthopaedic education. The purpose of this multicenter, blinded, randomized controlled trial was to determine the validity and efficacy of immersive VR training in orthopaedic resident education. Nineteen senior orthopaedic residents (resident group) and 7 consultant shoulder arthroplasty surgeons (expert group) participated in the trial comparing immersive VR with traditional learning using a technical journal article as a control. The examined task focused on achieving optimal glenoid exposure. Participants completed demographic questionnaires, knowledge tests, and a glenoid exposure on fresh-frozen cadavers while being examined by blinded shoulder arthroplasty surgeons. Training superiority was determined by the outcome measures of the Objective Structured Assessment of Technical Skills (OSATS) score, a developed laboratory metric, verbal answers, and time to task completion. Immersive VR had greater realism and was superior in teaching glenoid exposure than the control (p = 0.01). The expert group outperformed the resident group on knowledge testing (p = 0.04). The immersive VR group completed the learning activity and knowledge tests significantly faster (p < 0.001) at a mean time (and standard deviation) of 11 ± 3 minutes than the control group at 20 ± 4 minutes, performing 3 to 5 VR repeats for a reduction in learning time of 570%. The immersive VR group completed the glenoid exposure significantly faster (p = 0.04) at a mean time of 14 ± 7 minutes than the control group at 21 ± 6 minutes, with superior OSATS instrument handling scores (p = 0.03). The immersive VR group scored equivalently in surprise verbal scores (p = 0.85) and written knowledge scores (p = 1.0). Immersive VR demonstrated substantially improved translational technical and nontechnical skills acquisition over traditional learning in senior orthopaedic residents. Additionally, the results demonstrate the face, content, construct, and transfer validity for immersive VR. This adequately powered, randomized controlled trial demonstrated how an immersive VR system can efficiently (570%) teach a complex surgical procedure and also demonstrate improved translational skill and knowledge acquisition when compared with a traditional learning method.